Application of ISO standards on sampling and effects on the quality assessment of solid biofuel employed in a real power plant. (15th October 2020) - Toscano, G.; Leoni, E.; Feliciangeli, G.; Duca, D.; Mancini, M.
Abstract: Bioenergy is one of the main contributors in the renewable energy markets but the quality of solid biomass is often a concern. This study provides an application of the ISO 18135 on biomass sampling, evaluating how sampling procedure affects the analytical results and suggesting possible solutions to reach an acceptable level of precision for quality assessment. A sampling plan compliant with the aforementioned standard was carried out in a 21 MW biomass power plant located in Northern Italy in August and February, collecting samples of different typology from heaps stored in the plant and from trucks coming from suppliers. Moisture content analysis was performed for all the samples, and for those from heaps ash and nitrogen contents were also investigated. Considering moisture content, to achieve a good precision, a significantly different number of increments are needed in August and February. Regarding ash content, it would be impossible to obtain the precision suggested by the standard, because it would lead to a number of increments not in line with practical operations. Nitrogen content is not a concern in this case, because of the measured low values. In general terms, precision values suggested by ISO 18135 require a high effort by operator and resulted unsuitable in terms of practical application for moisture and ash contents. This is probably due to the different solid biomass considered during the standard development. For this reason, it is important to assess the quality of the different solid biofuels in order to tune the sampling procedure accordingly.